Influence of Dielectric Constants on Complex Equilibria Eu(III)-3(2-Hydroxy-5-Methyl Phenyl)-1-Phenyl-5-(4-Methoxy-Phenyl) Pyrazoline Complexes in Different Percentages of Methanol-Water Mixture - Meshram, Y.K. (Asian Journal of Chemistry, 2010)
The interaction between Eu(lIl) and 3-(2-hydroxy-5-methyl phenyl)- 1-phenyl-5-( 4-methoxy-phenyl) pyrazoline (HMPPMPPZOLINE) in different percentages of methanol-water mixture at 0.1 M ionic strength and 27 ± 0.1 °C has been studied potentiometrically. The data obtained can be used to study the values of proton-ligand and metal-ligand stability constants for 1 : 1 and 1 : 2 complexes. The effect of dielectric constants on stability constants of complex equilibria is studied in the present investigation.